Análisis financiero de la cooperativa de ahorro y crédito del instituto “Daniel Álvarez Burneo” de la ciudad de Loja periodo 2011 – 2012. - Calva Rosillo, Gonzalo Victoriano (2014)
This thesis entitled "Financial De La Cooperativa De Ahorro Y Credit Analysis from the Burnet Institute Daniel Alvarez De La Ciudad De Loja Period 2011-2012" it made with the purpose of fulfilling the objectives set in which they make reference vertical and horizontal analysis, as well as the implementation of the main financial indicators in order to determine the economic status and variation to each of the different accounts of the institution in the years that have been the focus of study. In compliance with the development of the thesis summarizes the results of the financial statements was performed, which allowed implement procedures that facilitated perform financial analysis and subsequent interpretation of the indicators of liquidity, profitability, delinquency and debt capacity between others, it possible to have a global view of the financial position in the years that have been evaluated. In conclusion it was known estimates and predictions about the possible economic conditions that will exist in the results of future periods, providing the directors make timely decisions favoring the development of the company. You should consider the institution of the application of financial analysis as a very useful tool to achieve projected future plans to provide more revenues to the company and through this an overview of how the institution is financially helping his policy to take appropriate decisions at any given time.